The Role Of General Pedagogy In The Preparation Of Future History Teachers For Test Activities (Texas Journal of Multidisciplinary Studies, 2025)
General pedagogy provides a framework for equipping future history teachers with the competencies necessary for testological work, including the ability to effectively design, implement, and evaluate assessments. This article examines how general pedagogical principles such as curriculum alignment, differentiated instruction, and learner-centered approaches contribute to the development of testological skills in teacher education programs. Combining theoretical foundations and practical methodologies, general pedagogy enables future teachers to address the specific challenges of evaluating history education, such as critical thinking and source analysis. The article concludes with recommendations for enhancing the role of general pedagogy in developing comprehensive testological competence in history teachers.